Ethylmalonic Encephalopathy ETHE1 R163W/R163Q Mutations Alter Protein Stability and Redox Properties of the Iron Centre - Henriques, Bárbara J.; Lucas, Tânia G.; Rodrigues, João V.; Frederiksen, Jane H.; Teixeira, Miguel S.; Tiranti, Valeria; Bross, Peter; Gomes, Cláudio M. (PLOS ONE, 2014)
ETHE1 is an iron-containing protein from the metallo β-lactamase family involved in the mitochondrial sulfide oxidation pathway. Mutations in ETHE1 causing loss of function result in sulfide toxicity and in the rare fatal disease Ethylmalonic Encephalopathy (EE). Frequently mutations resulting in depletion of ETHE1 in patient cells are due to severe structural and folding defects. However, some ETHE1 mutations yield nearly normal protein levels and in these cases disease mechanism was suspected to lie in compromised catalytic activity. To address this issue and to elicit how ETHE1 dysfunction results in EE, we have investigated two such pathological mutations, ETHE1-p.Arg163Gln and p.Arg163Trp. In addition, we report a number of benchmark properties of wild type human ETHE1, including for the first time the redox properties of the mononuclear iron centre. We show that loss of function in these variants results from a combination of decreased protein stability and activity. Although structural assessment revealed that the protein fold is not perturbed by mutations, both variants have decreased thermal stabilities and higher proteolytic susceptibilities. ETHE1 wild type and variants bind 1±0.2 mol iron/protein and no zinc; however, the variants exhibited only ≈10% of wild-type catalytically activity. Analysis of the redox properties of ETHE1 mononuclear iron centre revealed that the variants have lowered reduction potentials with respect to that of the wild type. This illustrates how point mutation-induced loss of function may arise via very discrete subtle conformational effects on the protein fold and active site chemistry, without extensive disruption of the protein structure or protein-cofactor association.